User Intention towards a Music Streaming Service: A Thailand Case Study - Debajyoti Pal; Tuul Triyason (My University, 2018)
This paper presents a novel acceptance model for an online music streaming scenario of Thailand. The music streaming industry has been gaining in popularity in the recent times. This research has been conducted in order to measure the user attitude towards the use of this relatively new service using a modified version of the popular Technology Acceptance Model. We try to identify the most popular music-streaming service of Thailand and also the factors that affect the use of such a service. Data has been collected in the form of an online questionnaire survey from more than 300 participants for the purpose of model building and validation. A subsequent regression analysis carried out on the proposed model explains more than 60 percent of the variance of the dependent variable i.e. Behavioral Intention in our case to the predictor variables Perceived Usefulness, Perceived Ease of Use, Perceived Enjoyment and Perceived Satisfaction Level. The results show that Perceived Enjoyment and Perceived satisfaction are the two strongest predictors for Behavioral Intention which is quite different from that of the utilitarian type of information systems.Keywords: Music streaming, TAM, hedonic information systems, regression
Keywords: Popularity; Technology Acceptance Model; Affect; External variable; Digital Marketing and Social Media